Development of low cost catalytic converter from non-precious metals - Mohiuddin, A. K. M. (IIUM Press, 2011)
The purpose of this chapter is to discuss the uses of non-precious metals for the development catalytic converters. Copper powder and nickel catalyst were chosen as the alternative catalysts to reduce the use of precious group metals (PGMs) platinum, palladium, and rhodium. Simulation by COMSOL has shmcvTI that Nickel and copper were very effective in reducing NOx during rich condition of air-fuel mixture while oxidizing CO and HC during lean condition. Simulations using FLUENT and COMSOL have sho\m the actual characteristics of the catalytic converter performance. The flow throughout catalytic converter and the backpressure have successfully determined. Furthermore, catalyst conversion efficiency also has been shown clearly. On the other hands, the experimental results have excellently validated the simulation results in terms of the nature and trends of the catalytic converter performance as well as its efficiency. Catalyst distribution and application of the non-zoning monolith substrates have further contributes to cut do'-"n the production cost.